2018
DOI: 10.4194/1303-2712-v18_1_02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We conducted a 71-day experiment to investigate the effects of stocking density in a recirculating aquaculture system (RAS) on the growth performance, body composition, digestive activity, and blood biochemical parameters of the marbled eel Anguilla marmorata. We stocked marbled eel in 1.0 m 3 tanks at stocking densities of 12, 20, and 28 kg/m 3 , which were designated the low-density (LD), medium-density (MD) and high-density (HD) groups. The fish weighed 169.72 ± 2.75 g at the baseline level. Results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
4
11
1
2
Order By: Relevance
“…When hens are exposed to overcrowding stress, they have greater energy requirements and plasma protein mobilization increases according to the intensity of the stress to meet energy demand. In response to stress, the total protein content in the blood may have been used as energy (Tan et al, 2018). As these enzymes are protein, the reduction in the activities of these enzymes in this study may be due to decreased protein content in the blood during high stocking.…”
Section: Effect Of High Stocking Density On Erythrocyte Antioxidantmentioning
confidence: 88%
See 3 more Smart Citations
“…When hens are exposed to overcrowding stress, they have greater energy requirements and plasma protein mobilization increases according to the intensity of the stress to meet energy demand. In response to stress, the total protein content in the blood may have been used as energy (Tan et al, 2018). As these enzymes are protein, the reduction in the activities of these enzymes in this study may be due to decreased protein content in the blood during high stocking.…”
Section: Effect Of High Stocking Density On Erythrocyte Antioxidantmentioning
confidence: 88%
“…Consistent with our results, Sahin et al (2014) indicated that high stocking density decreased hepatic SOD, CAT and GSH-Px activities in rainbow trout. It was demonstrated that blood total protein and albumin level significantly decreased in fish groups and broiler chickens reared at high stocking density (Najafi et al, 2015;C. It was demonstrated that blood total protein and albumin level significantly decreased in fish groups and broiler chickens reared at high stocking density (Najafi et al, 2015;C.…”
Section: Effect Of High Stocking Density On Erythrocyte Antioxidantmentioning
confidence: 99%
See 2 more Smart Citations
“…Son élevage en système intensif permettra de conserver, renforcer les stocks naturels et produire continuellement des spécimens de taille commerciale destinés à la vente sur les marchés. Dans les systèmes d'élevage intensifs, plusieurs facteurs à savoir la quantité et la qualité de l'aliment (Erondu et al, 2006) et la densité de mise en charge des poissons (Schram et al, 2006 ;Wirat, 2011 ;Chattopadhyay et al, 2012 ;Tan et al, 2018) influencent le taux de survie, la croissance, l'efficacité alimentaire et la production. La connaissance des besoins nutritionnels et des densités optimaux de mise en charge des alevins permettent d'améliorer la production et la rentabilité économique en aquaculture (Fiogbé et Kestemont, 2003 ;Aksungur et al, 2007;de Oliveira et al, 2012 ).…”
Section: Introductionunclassified